The alien characteristics of sea ice microbes : the potential for life on icy ocean worlds & beyond - Jayasinghe, SA (2022)
The characterisation of extraterrestrial environments has evolved over the past decades as more discoveries about astronomical objects in our solar system and the detection of exoplanets continues to enhance our understanding for the potential of life. These discoveries have broadened the definition of habitability, widening the concepts on what sort of extraterrestrial environments could potentially sustain life. The sea ice environment is analogous to some extraterrestrial habitats, such as the icy ocean moons Europa and Enceladus, and is populated by a variety of microbial organisms. These microorganisms must tolerate large variations in physiochemical parameters (e.g temperature, light, salinity, pH, nutrients, anoxia and dissolved gases), making them prime candidates to test the physiochemical limits to life. The primary aim of this thesis was to define the habitability potential of icy ocean worlds and other extraterrestrial environments. This was done using multiple physiological, molecular, and ecological techniques - culminating in a series of in situ laboratory experiments with polar microbes in simulated extraterrestrial conditions. The first chapter details the history, development and central philosophies of astrobiological research. A particular focus is given to the analogous nature of polar microbial environments to certain extraterrestrial habitats and why polar microbes are legitimate proxies for investigating the potential for extraterrestrial life. A central tenant of determining whether extraterrestrial sites are of astrobiological interest has been to "follow the water" that is finding planetary bodies with reservoirs of liquid water. However, the presence of water alone does not equate to life and to constrain the habitability potential of a water-laden world the chemical and physical characteristics also need to be investigated. The second chapter of this thesis explores the capacity for sea ice bacteria to adapt and grow under the different salinity constraints of Europa's subsurface ...